Second-generation laser balloon ablation for the treatment of atrial fibrillation assessed by continuous rhythm monitoring: the LIGHT-AF study. Issue 9 (9th April 2021) - Rovaris, Giovanni; Ciconte, Giuseppe; Schiavone, Marco; Mitacchione, Gianfranco; Gasperetti, Alessio; Piazzi, Elena; Negro, Gabriele; Montemerlo, Elisabetta; Rondine, Roberto; Pozzi, Mattia; Casiraghi, Mirko; De Ceglia, Sergio; et al.
Abstract: Aims: Balloon-based technologies have been developed to simplify catheter ablation of atrial fibrillation (AF), to improve the clinical outcome of the procedure and to achieve durable pulmonary vein isolation (PVI). The objective of this study is to evaluate the safety and efficacy of second-generation laser balloon (LB2) ablation in the treatment of AF using a continuous cardiac rhythm monitoring strategy. Atrial tachyarrhythmias (ATas) recurrences were assessed with implantable cardiac monitors (ICMs) or devices. Methods and results: All patients underwent LB2 ablation procedure. The primary endpoint was the first recurrence of any, >5.5 and >24 h duration ATas after the blanking period (90 days). In-hospital visits were performed at 3, 6, and 12 months. Seventy-three patients (68% male, mean age 59.8 ± 11.3) were included in the study. The average procedure, fluoroscopy, and laser ablation times were 81.5 ± 30.1, 21.5 ± 12.4, and 33.8 ± 9.7, respectively. All PVs were isolated using the LB2 with no need of touch-up using focal catheters. No major complications occurred during or after the procedures. The one-year freedom from recurrences was 66.9% (95% CI: 57.0–76.7%), 81.0% (69.5–88.5%), and 86.8% (76.1–92.9%) considering any, 5.5-h and 24-h cut-off duration, respectively. At 3, 6, and 12 months, any ATas was recorded in 22%, 32%, and 25% of patients, with a ≥5% arrhythmic burden documented in 4%, 5%, and 3%, respectively. Few patients reported AF-related symptoms (7%, 8%, and 5%). Conclusion: LB2 ablation is a safe and effective procedure, showing a high freedom from recurrences and low arrhythmic burden as documented by a continuous rhythm monitoring strategy.